The Antibacterial Activity Comparison between Novel Carbon-Based Nanofilm Coated Titanium Alloy and Co-Cr-Mo Alloy. (30th August 2022) - Ma, Tianying; Ran, Tianfei; Ke, Song; Qin, Yinyin; Wang, Min
Abstract : Objective . The purpose of this study was to reveal the antibacterial activity of carbon-based nanofilm titanium alloy. Methods . The experiments were performed both in vitro and in vivo of animals using two circular-piece test specimens of the same specification, which were made from carbon-based nanofilm coated titanium alloy and commonly used in artificial joints Co-Cr-Mo alloy, respectively. In the in vitro experiments, the two test specimens were cocultured with standard strains of Staphylococcus aureus and Escherichia coli, and the antibacterial properties of the two test specimens were evaluated via inhibition zone size, scanning electron microscopy, fluorescence staining, colony forming unit count, and others; the cytotoxicities of the two test specimens were evaluated by coculturing and them with rabbit bone marrow mesenchymal stem cells (BMSCs). In the in vivo experiments, the two test specimens were implanted in the muscle tissue of experimental rabbits to evaluate their histocompatibilities. Results . Both in vitro cocultures of the carbon-based nanofilm titanium alloy and the Co-Cr-Mo alloy with Staphylococcus aureus and Escherichia coli failed to form inhibition zone. However, some biofilms were observed on the surface of the Co-Cr-Mo alloy. Fewer bacteria adhered to the carbon-based nanofilm titanium alloy can be observed via scanning electron microscopy and fluorescence staining techniques. Meanwhile, the colony forming counts showed that, compared with the Co-Cr-Mo alloy, the carbon-based nanofilm titanium alloy had fewer bacteria adhered (P < 0.05 ). After coculture of the two test specimens with rabbit BMSCs, there was no significant difference in cell count, and both cell counts showed no cytotoxicity. In the in vivo experiment of animals, there are relatively fewer giant cells and better histocompatibility in tissues near the carbon-based nanofilm titanium alloy. Conclusion . Compared with Co-Cr-Mo alloy, the novel carbon-based nanofilm titanium alloy enjoys stronger in vitro antibacterial activity and better in vivo histocompatibility.